Fabrication of a "progress bar" colorimetric strip sensor array by dye-mixing method as a potential food freshness indicator. (30th March 2022) - Wang, Guannan; Huang, Shaoyun; He, Hui; Cheng, Jiawei; Zhang, Tao; Fu, Zhiqiang; Zhang, Shasha; Zhou, Yuzhi; Li, Houbin; Liu, Xinghai
Graphical abstract: A colorimetric strip sensor array was built by mixing bromophenol blue (BPB) and bromocresol green (BCG) with different ratios. Using NH3 as simulation gas, the color of the array turned from yellow to blue, and the number of the blue-colored spots were increased with the concentration rose, like a progress bar. It is concluded that the "progress bar" colorimetric strip sensor array can provide stable and accurate colorimetric results by transforming single color discrimination into color-recognizing and spot-counting. And mixing two pH responsive dyes with the same color-changing type is a feasible way for the "progress bar" colorimetric strip sensor array design which possesses the potential of becoming a new type of food freshness indicator. Highlights: Construction strategy of arranging ten ratios of BPB/BCG films within a certain order. The colorimetric effect is gradually blue diffusion, like a "progress bar" The colorimetric result can be obtained by counting the number of colored spots. The colorimetric results stayed stable under different lighting conditions. Can recognize five freshness states in the application of Cod packaging under 25 °C. Abstract: Colorimetric sensing is a low-cost, intuitive method for monitoring the freshness of food. We prepared a colorimetric strip sensor array by mixing different amounts of bromophenol blue (BPB) and bromocresol green (BCG). As results of NH3 simulation, the array strip turned from yellow to blue, and the number of blue spots increased with the increasing NH3, like a progress bar. Although the actual color is quite different, the color-changing trend was consistent with the simulated model calculated by a computer. The progress bar results remained stable under three lighting conditions. Furthermore, in the Cod preservation experiment, the color-changing progress of the strip sensor array is consistent with the simulation and can indicate Cod freshness while providing more distinguish levels. Therefore, a "progress bar" indicator built by this strategy possess the potential of realizing nondestructive, more accurate, and commercially available food quality monitoring through the naked eye and smart equipment recognition.